Ոգու մաքրագործման ասքեր (Գալշոյանի «Անթեղած ոգի» և «Օրիորդ Մարի» ակնարկները) - Երվանդյան, Զուխրա («Դիզակ պլյուս» հրատարակչություն)
В исследовании выражены наблюдения автора о реалиях сотворения Мушегом Галшояном идейно-художественной программы освещения национального духа. Мушег Галшоян, в числе внутренних жизненных субстанций которого были воспоминания исторической боли утраты и биологической тоски Эргира и эргирцев, в отмеченных очерках могучей силой художественного слова делает видимым несоизмеримость потерь, мучительных скитаний, резни и миграции, и историческую истину ужасной сущности геноцида. The research depicts the observations of the author concerning the reality of creating ideological and aesthetic program of illumination of national spirit by Mushegh Galshoyan. Mushegh Galshoyan, the inner existential substances of which include the memories of historical pain of loss and biological nostalgia of Ergir and people of Ergir, in the mentioned essays by means of strong power of a fiction word has made visible the incommensurability of losses, agonizing wanderings, massacre and migration, as well as the historical truth of genocide in its horrible essence.
Keywords: Բանասիրություն